Missionary Church, Colonial Church: the point of view of the Combonians of Nigrizia during the transition in Mozambique (1970-1975) (Tempo e Argumento, 2021)
This research aims to present the approach of the Italian Combonians in relation to the struggles for independence in the PALOP, with a particular emphasis for Mozambique. The Combonians have an old and significative presence in Africa and in Mozambique too, where, especially in the Centre and in the North, always accompanied their missionary action with a considerable proximity to local populations. In the period leading up to the obtaining of Mozambican independence, the Combonians leaded a movement of missionaries and other important figures inside local Catholic Church in order to favorite a radical change in the form of mission, as well as in the Church as a whole, breaking the traditional neutrality of the Catholics towards the Portuguese government and its policies. This article used a qualitative methodology, being focused on the analysis of the journal of the Italian Combonians Nigrizia between 1971 and 1975, and trying to understand their positioning in relation to the “colonial question”. It includes not only harsh criticisms towards Portuguese colonialism, but also towards the Portuguese and Mozambican Church, and in part also towards the Vatican hierarchies. This perspective made the Combonians “bet” in the new government leaded by FRELIMO, but without calculating the risks and the intolerances that the new Mozambican socialism perpetrated against the Catholic religion.Keywords: independence; Portuguese progressive catholicism; colonial violence; new mission.